Analyzing Cross-Linguistic Influence in Second Language Acquisition : A Bibliometric Study Using Vosviewer - Ratnasari Ratnasari; St. Asriati. Am; Dian Tanri Wulan; Syahruni Syahruni (Edumaspul: Jurnal Pendidikan, 2024)
This study aimed to determine the bibliometric data analysis of Cross Linguistic Influence in Second Language Acquisition using VOSviewer. It obtained the data through a reference management application. It used the keywords "Cross-linguistic, linguistic influence, language learning, and Second Language Acquisition" to search for data. Search data was taken from 2019 to 2023. The results showed that research data for five years obtained 219 articles. The number of studies every year fluctuates with a tendency to decrease. Most of the research occurred in 2019, with as many as 68 articles, and in at least 2023, as many as 4. The results of this study explain how important it is to use bibliometric analysis to discover the phenomena that occur regarding Cross Linguistic Influence in Second Language Acquisition. VOSviewer has analyzed numerous articles concerning the topic area, which is expected to stimulate researchers' enthusiasm in further developing research on this topic and function as a point of reference for upcoming material investigations